Quantum Computing, Blockchain Technology and its Future Impact on Library Encryption Standards in Nigerian Libraries: Quantum Computing, Blockchain Technology and its Future Impact on Library Encryption Standards in Nigerian Libraries - Dada, Kayode Sunday John (Talenta Publisher, 2026)
The rapid evolution of information technologies is ushering in a new era for academic libraries, characterized by the simultaneous emergence of quantum computing and blockchain technology. This research investigated how these innovations could transform information management practices in Nigerian higher education libraries. The study adopts a quantitative methodology, surveying 242 librarians, computer scientists, librarians, computing specialists, and information technology officers working in university libraries to assess readiness and perception. Conversely, block chain technology offers a decentralized, immutable framework for secure digital rights management, verified academic credentials, and transparent collection development. Findings show moderate support for quantum computing in data encryption (mean=3.36, SD=1.05), but stronger endorsement for Blockchain in collection transparency (mean=3.73, SD=0.98) and bibliographic management (mean=3.74, SD=0.91). Challenges dominate, with high agreement on costs (mean=4.40, SD=0.80), skills gaps (mean=4.32, SD=0.79), and power issues (mean=4.43, SD=0.85). The paper concludes that for Nigerian libraries to remain relevant and secure, they must transition towards post-quantum cryptography while leveraging block chain for data integrity Based on these findings, the study recommends immediate formation of a national consortium among Nigerian tertiary libraries to pool resources for pilot projects in block chain-based archiving and to develop a roadmap for quantum-resistant security upgrades and the need for library administrators to prioritize building partnerships with technology departments, seek external funding for infrastructure upgrades, and develop comprehensive training programs to equip staff with necessary technical competencies for managing next-generation security systems.